Terracottas of Bengal : an analytical study (with 276 illustration) - Haque, Zulekha, 1938- (Dhaka : International Centre for Study of Bengal Art, 2014)
On terracotta plaques in the archaeological sites found both in East and West Bengal. Studied in the context of history, society and its peoples.
"Updated version of ... [the author's] post-graduate dissertation done in the University of Oxford under the title, 'Terracotta decorations on the monuments of late mediaeval Bengal'"--Pref.
Includes bibliographical references (pages 333-340) and index.
AAL
Keywords: Terra-cotta sculpture, Indic -- India -- Bengal; Terra-cotta sculpture, Indic -- Bangladesh; Sculpture, Medieval -- India -- Bengal; Relief (Sculpture) -- India -- Bengal; Relief (Sculpture) -- Bangladesh; Clothing and dress in art; Jewelry in art; Bengal (India) -- Antiquities; Bangladesh -- Antiquities